Protecting the rights of refugees beyond European borders : establishing extraterritorial legal responsibilities / Lisa Heschl. - Heschl, Lisa (Intersentia, 2018)
The European migration and asylum policy has been shaped by efforts to establish an efficient migration management system in order to protect the Area of Freedom, Security and Justice from the new security threat of 'irregular migration'. The extraterritorialisation of immigration control measures beyond territorial borders form part of this strategy and the EU-Turkey deal and the call for an increased cooperation with Northern Africa are but two examples. Pre-border control mechanisms composed of administrative, legislative and operational measures, are largely perceived as effective means to channel flows of migrants avoiding logistical and financial burdens for Member States. However, from a legal perspective, this shift to extraterritorial activities raises important questions related to the creation of zones in which responsibilities for legal norms related to the protection of refugees may be circumvented by States or any other actors involved in migration control activities. Protecting the Rights of Refugees Beyond European Borders tries to reconcile the motives behind extraterritorialisation strategies with actual legal consequences. It carefully examines the legal frameworks that govern situations in which a migrant meets an authority in the context of extraterritorial immigration control measures. The book approaches the topic from the hypothesis that international and European obligations do not only constrain extraterritorial acts of States or specialised agencies, but give rise to concrete legal responsibilities deriving from different legal regimes such as general international law, human rights law and EU law. In addition, it takes a more practical approach going beyond the normative establishment of legal responsibilities by investigating the actual possibilities to invoke eventual responsibilities for violations of fundamental guarantees occurring in the context of extraterritorial immigration control measures. DR LISA HESCHL is a research and teaching fellow at the European Training and Research Centre on Human Rights and Democracy at the University of Graz (UNI-ETC). She has been a Marie Curie visiting fellow at the University of Deusto, Bilbao.